Insight on the stability of polycrystalline natural gas hydrates by molecular dynamics simulations. (1st April 2021) - Zhang, Zhengcai; Kusalik, Peter G.; Guo, Guang-Jun; Ning, Fulong; Wu, Nengyou
Graphical abstract: Highlights: The structures of hydrate grain boundaries and their stability were revealed. Hydrate grain boundaries exhibit complex cage structures and gas bubbles. Grain structures and guest types both affect the thermal stability of hydrates. CO2 molecules can greatly accelerate the dissociation of hydrates. Abstract: Gas hydrates have drawn considerable attention in the globe because of their importance in environment and energy field. Although the hydrates in nature and synthesized in the laboratory are polycrystalline materials, the structures of their grain boundaries, their stability, and the influence of the grain boundary structures on hydrate dissociation remain unclear. In this study, we conducted massive simulations of CH4 and CO2 hydrates to investigate these issues. We find the grain boundaries of polycrystalline natural gas hydrates exhibit complex cage structures featuring nonstandard cages and may contain small gas bubbles. The boundaries can be periodically connected by repeated cage motifs of defect cages containing 4- and 8-membered rings. Examining the thermal stability of these grain boundary structures, our results show that for polycrystalline CH4 hydrates, the dissociation process at the grain boundaries can be hindered, where annealing of the grain boundary structure can further enhance this effect. Consequently, polycrystalline CH4 hydrates are found to dissociate only when the temperature is somewhat above the bulk melting temperature, but not the case for polycrystalline CO2 hydrates. This indicates that the grain boundary structures and guest types both affect the thermal stability of polycrystalline hydrates at the grain boundaries. Moreover, we also investigated the dissociation process of polycrystalline hydrates, we find that CO2 molecules can greatly accelerate the dissociation of hydrates because CO2 molecules can induce the formation of gas bubbles and prefer to be in gas bubbles, and that the dissociation process initiates with the decomposition of 5 12 6 2 cages.